Reasons for public to back equity-based crowdfunding in Malaysia - Chew, Pei Chin; Chan, Phui Yee; Low, Yan Qing; Tan, Tze Yi (2024)
This study examines the backing intention of the public towards equity-based crowdfunding in Malaysia. The Social Cognitive Theory (SCT) has been utilized in conducting the research model of this study. SCT includes the behaviour, personal factors and environmental factors which are suitable for this study to investigate the independent variables which are backing self-efficacy, rewards, website service quality and perceived risk. Additionally, Malaysians who are 18 years old and above are the target respondents in this study. A total of 403 responses were gathered for the purpose of data analysis. The data information was analysed by using SPSS 26.0 software. The analysis comprises a few elements which included Cronbach’s Alpha, multicollinearity test, normality test, Q-Q plot and multiple regression analysis. The study findings revealed that backing self-efficacy, rewards and website service quality are significantly related to the public intention to back equity-based crowdfunding in Malaysia. Nevertheless, the relationship between perceived risk and backing intention of Malaysians towards equity-based crowdfunding is insignificant. Furthermore, this paper would demonstrate a comprehensive understanding on equity-based crowdfunding which helps in enhancing crowdfunding knowledge towards Malaysians as well as increasing the involvement in equity-based crowdfunding projects.